Analisis Arrester Sebagai Sistem Proteksi Pada Transformator di Gardu Induk Keramasan - Hermawanto Hermawanto; Irine Kartika P; Perawati Perawati; Yudi Irwansi (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Lightning overvoltage is a periodic overvoltage caused by external causes. An arrester is equipment that protects installations from overvoltage disturbances due to lightning strikes or electrical surges. The transformer functions to distribute electrical power by increasing or decreasing the voltage at the substation. This research focuses on substation equipment, namely the type 3EP 2150-2PL3 arrester connected to a 100 MVA IBT Transformer. Good protection is obtained if the arrester is placed as close to the transformer as possible. Therefore, this distance is determined so that protection can take place properly. The distance between the arrester and the transformer used at the Keramasan 150 KV substation is 5 m. while from the calculation results it is 22.5 m. based on SPLN 7: 1978 that for a 150 kV system the distance between the lightning catcher and the transformer does not exceed 80 m. This means that the distance between the arrester and the 100 MVA IBT Power Transformer is still within the limits set by PT PLN. The continuity of the spark that occurs in the arrester is still within safe limits and in accordance with mathematical analysis.